DIFFERENCES OF BONE REGENERATION USING BOVINE HYDROXYAPATITE AND BOVINE HYDROXYAPATITE WITH FREEZE-DRIED PLATELET RICH PLASMA ALLOGRAFT IN BONE DEFECT OF FEMORAL WHITE RABBIT - Mouli Edward; Henry Dominica; Ferdiansyah Mahyudin; Fedik Abdul Rantam (Journal Orthopaedi and Traumatology Surabaya, 2020)
Background: Hydroxyapatite is a bone graft that has osteoconductive properties for bone defects treatment. Platelet-rich plasma (PRP) has a capability of providing many bioactive molecules in physiological proportions. Hydroxyapatite given freeze-dried PRP is expected to create a graft that can strengthen the matrix while promoting osteoinduction. This study compares the effects of regeneration on the bone between bovine hydroxyapatite (BHA) and bovine hydroxyapatite with freeze-dried platelet-rich plasma (FD-PRP) as a bone graft in bone defect of the femoral white rabbit.Methods: The 12 equal New Zealand white rabbits aged 6-9 months are divided into two groups. Bone defects were made in the lower femoral meta-diaphysis with a diameter of 2.5 mm. The defects were filled with BHA with FD-PRP allograft in the treatment group and BHA in the control group. Both groups will be sacrificed in the third and sixth weeks, then evaluated histologically for microvascular structure, osteoblasts, woven bone, type-I collagen, osteocalcin, alkaline phosphatase, and immunoglobulin G.Results: During the evaluation in week 3 and 6, microvascular structure, osteoblast, and type-I collagen decreased in both groups with insignificant differences (p>0.05). Woven bone, osteocalcin, and immunoglobulin G increased in the treatment group but was not significant (p>0.05). Alkaline phosphatase increased higher in the treatment group, with a considerable difference in the sixth week (p=0.008).Conclusion: The elevation in the production of woven bone, osteocalcin, and alkaline phosphatase at the third and sixth-week evaluations highlight the possibility that administering BHA given FD-PRP may have contributed to the healing of bone defects.